Competitive Information in the Stock Market: An Empirical Study of Earnings, Dividends and Analysts' Forecasts: Discussion - Sunder, S. (Journal of Finance, 1976)
S. Sunder, Competitive Information in the Stock Market: An Empirical Study of Earnings, Dividends and Analysts' Forecasts: Discussion, The Journal of Finance, Vol. 31, No. 2, Papers and Proceedings of the Thirty-Fourth Annual Meeting of the American Finance Association Dallas, Texas December 28-30, 1975 (May, 1976), pp. 680-684